PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN LIKUIDITAS TERHADAP HARGA SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2022-2024 - Merry Agustin; Ida Subaida; Nanda Widaninggar (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
Mining in Indonesia has undergone changes through the implementation of downstreaming policies aimed at increasing the added value of domestic commodities, thus causing changes in the Indonesian mining industry. This study aims to examine the effect of capital structure, profitability, and liquidity on firm value, with stock price as an intervening variable, in mining companies listed on the IDX in 2022-2024. This study used a purposive sampling technique, resulting in 12 companies as samples. Data were obtained from annual financial reports available on the official website of the Indonesia Stock Exchange. Data analysis used Smart PLS 3.0. The data analysis methods used in this study included classical assumption tests, coefficient of determination tests, structural equation analysis (inner model), and research hypothesis testing. The results of direct hypothesis testing indicate that capital structure has a negative but insignificant effect on stock price, profitability has a positive but insignificant effect on stock price, and liquidity has a negative but insignificant effect on stock price. Capital structure has a positive but insignificant effect on firm value, profitability has a positive but significant effect on firm value, and liquidity has a positive but insignificant effect on firm value. Furthermore, stock price also has a positive but insignificant effect on firm value. The results of the indirect hypothesis test indicate that capital structure has a negative but insignificant effect on firm value through stock price, profitability has a positive but insignificant effect on firm value through stock price, and liquidity has a negative but insignificant effect on firm value through stock price.